Normes scolaires et normes professionnelles à l'épreuve des troubles du comportement ? - Rachel Gasparini (Nantes Université, 2019)
As for as "behavior problems" are considered a major disturbance of the ordinary school situation (physical and verbal aggression towards children or adults, material deterioration, dangerous conducts towards oneself) they are a major destabilizing factor to primary school teachers. One may wonder to what extent professional standards are being questioned in kindergarten (place where school standards are first confronted), particularly by the unexperienced teachers. The data were obtained from two investigations: in the first trainee-teachers were asked about their authority; in the second, professionals working with young children with "behavior problems" were interviewed.